Joint management in action - George River caribou herd - Andersen, Chesley; Rowell, Judy (Rangifer, 1991)
This paper is about a major caribou herd that may be in trouble and the belief of the Labrador Inuit Association (LIA) that the biggest current threat to the health of the herd may be the management policies of governments.